1992
DOI: 10.1136/vr.131.20.464
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens in dog bite wounds in dogs in Harare, Zimbabwe

Abstract: Over a year swabs were taken from 87 untreated bite wounds in dogs seen by veterinary practitioners in Harare, Zimbabwe. Swabs were also taken from normal skin adjacent to the wound site, and gingival swabs were collected from normal dogs coming to the same clinics. The swabs were cultured aerobically for pathogens, particularly Staphylococcus intermedius, and the antibiotic sensitivities of the pathogens were determined by disc diffusion assay. The most common pathogens isolated from the wounds were S interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
6
18
0
Order By: Relevance
“…Microbiological investigation revealed isolation of strains of Staphylococcus aureus, Pseudomonas aeruginosa, E.coli, Klebsiella spp., Protius, Bacillus, Clostridium, Streptococcus, Micrococcus and Fusobacterium from different wounds from various species. Our result of bacterial isolation is in support with earlier reports of other workers (Goldstein, 1992;Kelly et al, 1992;Jousmies-Somer et al, 1995;Qureshi et al, 2002;Dierikx et al, 2012;Escobar et al, 2013). In the present study performed over animals for wounds among significant isolates Staphylococcus aureus was the most common isolate (36.22%) followed by E. coli from 34.59 % cases and showed different pattern of sensitivity as evident from the Table 2 and 3.…”
Section: Discussionsupporting
confidence: 82%
“…Microbiological investigation revealed isolation of strains of Staphylococcus aureus, Pseudomonas aeruginosa, E.coli, Klebsiella spp., Protius, Bacillus, Clostridium, Streptococcus, Micrococcus and Fusobacterium from different wounds from various species. Our result of bacterial isolation is in support with earlier reports of other workers (Goldstein, 1992;Kelly et al, 1992;Jousmies-Somer et al, 1995;Qureshi et al, 2002;Dierikx et al, 2012;Escobar et al, 2013). In the present study performed over animals for wounds among significant isolates Staphylococcus aureus was the most common isolate (36.22%) followed by E. coli from 34.59 % cases and showed different pattern of sensitivity as evident from the Table 2 and 3.…”
Section: Discussionsupporting
confidence: 82%
“…Investigators commonly report that no single antimicrobial or antimicrobial combination is effective against all species of bacteria cultured from bite wounds . Our study found similar results with a majority of patients initially receiving the empirically chosen combination of ampicillin and enrofloxacin.…”
Section: Discussionsupporting
confidence: 80%
“…The documented contamination rate of bite wounds lies between 48% and 95.8%, with a wide variety of different bacteria encountered (Kelly et al . , Griffin & Holt , Meyers et al . , Mouro et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study 62.3% of the patients were presented with contaminated wounds and the bacterial species identified generally resembled previously published data (Kelly et al . , Griffin & Holt , Meyers et al . , Mouro et al .…”
Section: Discussionmentioning
confidence: 99%